Curieux objet de genre, le livre et sa place dans des inventaires après décès à Lille au XVIIIe siècle - Aurore Pinceel (Genre & Histoire)
Does the post-mortem inventory still have anything to teach us? The source, very well-known to historians of material culture and the book of the modern period, is certainly one of the best examples of the importance for gender historians to rethink the methodological tools available in order to process documents that, at first glance, appear to have revealed all their secrets. Using the case of the book-object as a starting point, the article proposes to revisit the paradox that almost systematically results from attempts to use inventories to identify the presence in domestic space of objects that are culturally gendered but rendered statically neutral by the treatment of the source. A more detailed analysis of the document shows that, far from constituting homogeneous groups of readers, the men and women who owned books diverged on at least three points—the number, the subject matter and the spatial location of their books—all of which testify to the contrasting relationships men and women had with regard to written culture in the modern era.